2004
DOI: 10.2320/matertrans.45.3286
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Glass Beads from Molten Slag Produced by Rotary Cup Atomizer

Abstract: Steelmaking is well known to be one of the highest energy-consuming industries, where high temperature molten slag is discharged without any heat recovery. This paper describes the hot experiments where a Rotary Cup Atomizer (RCA) is used to produce dry glassy slag without water impingement. In this, the properties for granulated slag were chiefly investigated. Molten slag was first poured onto the center of the rotating cup at various rotating speeds. Slag granulation was then observed using a video camera, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…One promising heat resource that can be recovered is the waste heat of steelmaking slag, which has both a higher temperature and a higher calorific value than other types of waste heat and is unused in the current process. Although many slag heat recovery processes, including air atomizing [3][4][5][6] and mechanical atomizing, [7][8][9][10] were tried previously, 11,12) most were not successful at the industrial scale due to the instability of the physical properties of slag, such as viscosity, which changes drastically depending on both the temperature and the chemical composition of the slag. Furthermore, the heat conductivity of slag is also relatively low compared with that of other materials like coke, from which heat is recovered by coke dry quenching (CDQ), and this reduces the efficiency of heat recovery from a packed bed of slag particles.…”
Section: Introductionmentioning
confidence: 99%
“…One promising heat resource that can be recovered is the waste heat of steelmaking slag, which has both a higher temperature and a higher calorific value than other types of waste heat and is unused in the current process. Although many slag heat recovery processes, including air atomizing [3][4][5][6] and mechanical atomizing, [7][8][9][10] were tried previously, 11,12) most were not successful at the industrial scale due to the instability of the physical properties of slag, such as viscosity, which changes drastically depending on both the temperature and the chemical composition of the slag. Furthermore, the heat conductivity of slag is also relatively low compared with that of other materials like coke, from which heat is recovered by coke dry quenching (CDQ), and this reduces the efficiency of heat recovery from a packed bed of slag particles.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the calculated data and experimental one 15) shows the validity of the model for predicting the drop diameter. The agreement is reasonably good, except for experimental condition below 16.6 s À1 of rotating speed.…”
Section: Temperature Distribution Of a Single Particlementioning
confidence: 99%
“…The number of the ligaments around the disk, K, was estimated using Kitamura's eqs. (13) to (15) under the operation conditions; additionally, the physical properties of the liquid slag and then the film thickness were also calculated. Accordingly, by substituting eq.…”
Section: Physical Model Of Ligament Formationmentioning
confidence: 99%
“…These theoretical results are consistent with the result of Purwanto et al which found fracture of RCA slag (amorphous) required ~1.82 times more energy than water-impinged slag (ostensibly a mixture of IG, GB, and IP fractures). 36) In slags solidified moderately quickly (e.g., water impinged, pit cooled), the polycrystalline structure results in the potential for IP, GB, and IG fractures. Though grain boundaries are plentiful, there is a random distribution in the alignment of grain boundaries to the application of force.…”
Section: )mentioning
confidence: 99%